Sacred designs: the rich history of British mosques - Heathcote, Edwin (FT.com, 2021)
First built as a chapel by French Huguenots in 1743, it was taken over by Wesleyans, then Methodists and became a synagogue in 1891, converted by refugees from the pogroms in Russia and eastern Europe. A building conceived by French immigrants in an English i diom adapted by Muslims from Bangladesh in a street where curry houses mingle with vintage stores and graffitied bars, is now at the centre of Three British Mosques, an exhibition at the Venice Biennale of Architecture in collaboration with the V&A. Christopher Turner, the museum’s keeper of design, architecture, and digital, suggests that transporting this hybrid building to Venice, a city which he says Ruskin described as a city of Arab splendour, a place where east meets west, allows the museum to look at this condition of an embedded architecture of immigration. Shahed Saleem, an architect and author who has written a book about the subject, is co-curator of the exhibition.